Efektivitas dan Akuntabilitas Dana Pokir dalam Perencanaan Pembangunan Daerah: Studi Kualitatif dari Perspektif Stakeholder Lokal Di Kabupaten Sumbawa - Komala, Rina; Ihyani, Layali (Universitas Mataram, 2025)
The purpose of this study is to analyze the effectiveness and accountability of the use of Main Funds (Pokir) in the development planning process of Sumbawa Regency. A qualitative approach is used in the case study method through interviews, participatory observation, planning and report analysis. The results of the study indicate that Pokir funds can meet community efforts and improve the representation capacity of the DPRD, but still face various challenges including lack of transparency in the proposal process, weak monitoring mechanisms, and limited coordination between related institutions. Accountability for the use of Pokir funds often depends on individual initiatives and is not fully supported by a solid system. Therefore, to improve the effectiveness and accountability of Pokir Funds, institutional reforms are needed, strengthening the planning information system and more active community participation. This study contributes to improving the understanding of the management of Pokir Funds in Sumbawa Regency which is more responsive and integrative.